Impact of the early 2020 COVID-19 crisis and lockdown on PrEP use among men who have sex with men (MSM) in France. (11th February 2022) - Di Ciaccio, Marion; Villes, Virginie; Michels, David; Morel, Stéphane; Delabre, Rosemary M; Rojas Castro, Daniela; Velter, Annie
Abstract : Objective: To describe changes in pre-exposure prophylaxis (PrEP) use during and following the COVID-19 lockdown in France (March–May 2020) and identify the factors associated with PrEP discontinuation among men who have sex with men (MSM) after the lockdown. Methods: Data from the, an anonymous, cross-sectional internet survey among MSM in July 2020, were analysed. Among respondents who were using PrEP prior to the lockdown, a binary logistic regression model was used to compare participants who were still taking PrEP (current PrEP users) with those who were not taking PrEP at the time of the survey (former PrEP users). Results: Among 8345 respondents, 946 were PrEP users before the lockdown, of whom 58.8% (n=556) reported stopping PrEP during the lockdown and 15.4% (n=146) were not using PrEP at the time of the survey. Among the 556 who stopped PrEP during lockdown, 86.5% (n=481) reported no sexual activity; 76.8% (n=427) restarted PrEP after lockdown. Former PrEP users were more likely to be younger, not living with a stable male sexual partner, report moderate anxiety, report increased psychoactive drug use during the lockdown, and report not having tested for HIV or STI since the end of the lockdown because they did not know where to go, preferred to wait or for another reason. Reporting fewer male sexual partners in the last 6 months was also significantly associated with being a former PrEP user. Conclusions: MSM adapted PrEP use to their sexual activity during and after the French lockdown. After the lockdown, discontinued PrEP occurred more often among MSM who had fewer sexual partners and had mental health vulnerabilities. These factors could also be predictive of PrEP discontinuation in a more general context. PrEP users should be informed on how to safely stop/start PrEP and on the use of other prevention tools to reduce potential risk exposure during PrEP discontinuation.